-8x-3=4x+9

Simple and best practice solution for -8x-3=4x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-3=4x+9 equation:


Simplifying
-8x + -3 = 4x + 9

Reorder the terms:
-3 + -8x = 4x + 9

Reorder the terms:
-3 + -8x = 9 + 4x

Solving
-3 + -8x = 9 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + -8x + -4x = 9 + 4x + -4x

Combine like terms: -8x + -4x = -12x
-3 + -12x = 9 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + -12x = 9 + 0
-3 + -12x = 9

Add '3' to each side of the equation.
-3 + 3 + -12x = 9 + 3

Combine like terms: -3 + 3 = 0
0 + -12x = 9 + 3
-12x = 9 + 3

Combine like terms: 9 + 3 = 12
-12x = 12

Divide each side by '-12'.
x = -1

Simplifying
x = -1

See similar equations:

| a+4b= | | 2x-8+7= | | 6a+9b= | | 7.3x-3.1=11.5 | | 5t^2-15+2=10 | | 8a+3b= | | X^2+2x=60 | | 7x+5(x+2)+4= | | 3p+5=30p | | 4(logx-1)=18 | | 16x^4+16x^2+3=0 | | 12a+15b= | | (7x-4)(7x+5)= | | 3v+w+8-2v+2= | | -2-17-22=2y+3(y-6) | | -5+(19)+(-34)+44= | | 2x+5x^4+6=0 | | 8(4x+4)= | | -6(x+3)+2x+6=8x+7 | | 20*7-4*7= | | -16t^2+144t-160=0 | | 15w+21=3(5w-7) | | -5+200=100 | | 3y^2-6y-24= | | -3+3(z-2)=(-7z+3)-6 | | 3x=cos(0.5x) | | 18=6v | | 4u-7u=-1-14 | | 5(-3-6n)=195 | | 4x^2-4x-48= | | (x+4)(xy-6)=7x | | 16x^2+-40x+25=0 |

Equations solver categories